Historical blocking: IN 2019-12-20 (India) - Voidly (2019)
WARNING severity censorship detected in India. Confidence: 74%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: IN-2019-0003
Keywords: censorship; IN; censorship; warning